Impacts of Household Wastewater on the Environment: The Case of Debre Markos Town, Amhara Regional State, Ethiopia - Abebaw, Maru (Asian Journal of Social Sciences and Management Studies, 2014)
The study is conducted in Debre Markos Town which is the capital of East Gojjam Administrative Zone. The paper aims at assessing the impacts of household wastewater management on environment. The existing household wastewater management in the Town is very poor and creates adverse impact on environment like health problem, river and air pollution. These are due to shortage of vacuum trucks to empty toilet, absence of central sewer system, improper drainage systems of household wastewater, low income and lack of awareness of the community to manage household wastewater are the common problems in the Town. As the result, the community discharges household wastewater in to open space, river and streams. Both primary and secondary data were used. The existing household wastewater management condition, the impact of inadequate household wastewater management and challenges were evaluated after findings based on the household survey of 162 sample respondents, interview and field observations. Microsoft-excel were used to present and analyze; and bar graph, pie chart and tables, percentages and figures were used. The results of the study included: the existing household wastewater management services was inadequate, health problem, river, stream and air pollution are impacts of improper management of household wastewater, insufficient infrastructure, lack of coordination between institutions, inadequate participation of stakeholders and lack of community awareness are challenges to manage household wastewater in the Town. Based on findings of the result and the case study; increase inaccessibility of household wastewater management facilities, creating awareness to community, coordination and integration among institutions, participation of stakeholders and provide sewerage system are the recommendations forwarded in order to promote proper household wastewater management system in the Town.